New data on the genus Barsine Walker, 1854 from India, with description of a new species (Lepidoptera: Erebidae: Arctiinae: Lithosiini) - Joshi, Rahul; Singh, Navneet; Volynkin, Anton V. (Zootaxa, 2018)
A new species, Barsine pseudoradians Joshi, Singh & Volynkin sp. nov. is described from North East India (Mizoram, Assam and Meghalaya) and Nepal. The new species belongs to the Barsine prominens (Moore) species-group and is compared with B. radians (Moore, 1878), B. pluma Černy, 2009, B. syntypica Swinhoe, 1906 and B. maculifasciata (Hampson, 1894). Barsine callida (Fang, 1991) is reported for the first time from India. Its comparison with the related Barsine mesortha (Hampson, 1898) is given. Two new combinations are established: Barsine callida (Fang, 1991), comb. nov. and Barsine germana (Rothschild, 1913), comb. nov. Adults, male and female genitalia of all the reviewed species are illustrated.